(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Stroke is a chronic disease requiring patients to be treated for a long period of time. Patients need to been given close and attentive care, and this has an impacton the health and daily lives of caregivers. The aim of this cross-sectional descriptive study was to investigate the quality of life of stroke patient caregivers at Srinagarind Hospital, Khon Kaen Province, Thailand. The subjects were 166 caregivers of all stroke patients who received treatment at Srinagarind Hospital during the period 1 July 10 September, 2011. The research tool was a questionnaire which was intwo parts: Part 1 was designed to collect baseline data about the patients and their caregivers, and Part 2 was the Thai version of the brief WHO quality of life assessment instrument (WHOQOL-BREF-THAI). Data were collected from the patients medical histories and from interviews conducted by the researchers and were analyzed using descriptive statistics. The results showed that the overall quality of life of caregivers was at a moderate level with a mean score of92.5. In terms of each component domain of the quality of lifeinstrument, the mean scores for physical health, mental health, social relationships, and the environment were24.1, 21.3, 10.7, and 29.3 points, respectively.Even though the quality of life of caregivers was moderatelyhigh, medical professionals who provide care for stroke patients should assist and support caregivers in various ways by, for example, giving advice on sources of information which are useful to the caregivers themselves and for the physical and mental health care of the patients in. They should also provide assistance to families when they require help in continuing to care for the patients in their own homes.